Design of embedded parallel resonant circuit multiband microstrip patch antenna for tablet PC - Islam, Md. Rafiqul; Abdullah, Khaizuran; Mohammad Shawkat, Habib (2014)
Among different types of antennas, the microstrip patch antennas (MPA) are the center of extensive research interest as the increasing demand for wireless applications are at its peak. To accommodate the need of space for different components in sleek handheld devices like the tablet PC, the MPAs are one the best option. In this paper various structures that are able to demonstrate the multiband characteristics are presented and the comparison of performance depending on the return loss, size are to be discussed along with a proposed design operational for GSM and LTE applications.